EMPAT PULUH SATU JUTA PENDUDUK INDONESIA MENGALAMI DEFISIT ENERGI - Iman Sumarno (Persagi, 2005)
ABSTRACTBackground: Food consumption deficit in energy causes negatif impact to the quality of human resources from fetus, growth and to adult. The last estimation of population of energy deficit was conducted in 1989 by Suryana et. al. Economic crisis may increase the number of people with energy deficit. Objectives: To estimate the number of people deficit in energy based on Susenas 2003 data. Methods: The number of people with deficit energy has been estimated using the publication of Central Bureau of Statistics (CBS) on the consumption of energy by expenditure classes from SUSENAS 2003. Deficit energy is defined as 70% of average RDA of Indonesian population. The distribution of energy consumption in each expenditure class is assumed normal. The area below 1540 kilo calorie is the proportion of people deficit energy in each expenditure class. The standar deviation was estimated based on the previous consumption surveys. Results: It is estimated, at least 41 million Indonesian suffer from deficit energy. Among them 25,7 million or 6,1 million households were deficit energy due to economic reasons. They are the target of rice for the poor in addition of income generating program. [Penel Gizi Makan 2005,28(1): 23-30] Keywords: food consumption, poverty